Powder technology in plastics processing - Wong, Anthony Chi-Ying (Carl Hanser Verlag, 2021)
Industrial processes involving handling of solid raw materials are highly dependent on our understanding of the fundamental characteristics and properties of the starting solid materials, as well as whether or not the related process hardware and operation are properly designed and optimized. This is true of almost all plastics manufacturing processes since particulate solids handling is the most elementary processing step. This book provides a broad understanding of powder technology and the significance of particulate solid characteristics that are applicable to plastics manufacturing processes. It focuses on the particular characteristics of solid materials relevant to plastics manufacturing processes. Applications of engineering principles based on the selected solid characteristics which illustrate the uniqueness of the subject are also included. The useful and practical information within offers engineers solutions to otherwise unclear problems commonly encountered in industry. The selected examples of research investigations provided should also inspire readers to formulate further fundamental as well as applied research studies on the inter- and intra-relationship between powder technology and plastics processing technology. Contents: - Introduction - Polymers, Additives, and Processing - Fundamental Parameters of Powder Characteristics - Solid-Solid Mixing - Storage and Discharge of Particulate Solids - Pneumatic Conveying of Particulate Solids - Gas Fluidization - Interparticle Forces - Effects of Particle Characteristics on Rheological Properties of Polymeric Melts.